برامج التكييف الاقتصادي وفقا للمنظمات الدولية وأثارها على الدول النامية - محمود, يوسف عبد العزيز (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعتبر برامج التكييف الاقتصادي التي تبناها كل من صندوق النقد الدولي والبنك الدولي من أكثر القضايا إثارة للجدل في الوقت الراهن، وذلك من خلال تبنيها من قبل أكبر المنظمات الاقتصادية الدولية وهي صندوق النقد الدولي والبنك الدولي، وقد ترافق ذلك مع أزمة المديونية الخارجية بالنسبة للعديد من دول آسيا وإفريقيا وأمريكا الشمالية. سنعمد في هذه الدراسة إلى عرض الجدل المثار حول برامج التكييف الاقتصادي والتعريف به وأجزائه ولمحة تاريخية عنه، والأهداف المعلنة والمخفية لسياساته وبرامجه (سياسات جانب الطلب وسياسات جانب العرض والسياسات الاجتماعية)، ونأخذ مثالاً تجربتي المكسيك ومصر في مجال التكييف الاقتصادي. سوف نقوم بتعريف التكييف الاقتصادي والروابط بين البنك الدولي وصندوق النقد الدولي في مجال برامج التكييف الاقتصادي، ثم نقوم باستعراض أهم أهداف برامج التكييف الاقتصادي من تحقيق النمو الاقتصادي وتخفيض التضخم إلى الوصول إلى توازن ميزان المدفوعات، وتحسين كفاءة استخدام الموارد الاقتصادية، وإنقاذ البنوك الدائنة للدول النامية بالإضافة إلى فتح أسواق الدول النامية أمام منتجات الدول المتطورة، ثم نستعرض أهم إجراءات برامج التكييف الاقتصادي، وذلك من خلال دراسة سياسات جانب الطلب وسياسات جانب العرض بالإضافة إلى السياسات الاجتماعية. كل ذلك بهدف الوصول إلى استنتاج الآثار الاقتصادية والاجتماعية الناجمة عن تطبيق برامج التكييف الاقتصادي في الدول النامية. The programs of economic conditioning، which was adopted by the International Monetary Fund and World Bank Group are the most critical problems in this time. This was associated by external indebtedness crisis for many of the countries in Asia، Africa and North America. We will study the controversy about the economical conditioning programs: we will define it and its parts، its historical background، the declared and hidden objectives for its programs, and policies (the policies of demand side and the policies of supply and the social policies). We will take، as examples، the experiments of Mexico and Egypt in the field of the economic conditioning. We will define the links between the Monetary Fund and World Bank Group in the field of economic conditioning programs. Then we will present the most prominent objectives of economic conditioning programs which are achieving the economic growth، reduction of inflation to get to balance of payments، improving the efficiency of using the economic resources، saving the indebted banks in the developing countries in addition to opening the markets of the developing countries for the products of the developed countries. Then we will present the procedures of the economic conditioning by studying the policies of demand and the policies of supply in addition to the social policies. All this is to deduct the economic and social effects resulting from implementation in the developing countries.